The Organizational Context of User-Centered Software Designs* - Kling, Rob (MIS Quarterly, 1977)
Many computer programs that are technically well designed fail to meet the human or organizational purposes they were expected to serve. Prevailing design methodologies stress either special technical devices or policies of involving people in the design of software they will use. Several user- oriented design strategies and their limitations are discussed. An expanded conceptual framework which includes both the personal characteristics of designers and features of the organizational settings in which they work is presented. The framework is used to develop a set of policies for practitioners to help foster the development of user-centered systems.